Polyformaldehyde composition material and preparation method thereof
By using composites of stearate, metal oxide and hydrated magnesium aluminum inorganic salts and vinyl polyethylene glycol ether as anti-penetrating agents in polyformaldehyde materials, the problem of insufficient fuel resistance and acid resistance of polyformaldehyde materials is solved, efficient improvement of fuel resistance and acid resistance, and the thermal stability and hue of the material are improved.
Patent Information
- Application Number
- CN202411685287.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-07
AI Technical Summary
When existing polyformaldehyde materials are exposed to fuel oil or acidic media for a long time, they have poor fuel resistance and acid resistance, resulting in limited application in automotive fuel systems.
The composite of stearate, metal oxide and hydrated magnesium aluminum inorganic salt is used as the composite acid absorbing antacid, and combined with vinyl polyethylene glycol ether as the anti-penetrating agent, the synergistic effect of copolymerized polyformaldehyde resin and other additives is used to improve the fuel oil and acid resistance of polyformaldehyde.
It significantly improves the fuel retention and acid retention of polyformaldehyde to reach more than 80%, while improving its thermal stability and hue, keeping it in white or light yellow, suitable for high-demand automotive fuel system components.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of polymer materials, and in particular to a polyoxymethylene composition material and a preparation method thereof. Background Art
[0002] Polyoxymethylene (POM) is a highly crystalline thermoplastic engineering plastic. The chemical structure of polyoxymethylene is mainly composed of repeated -CH2-O- units. It has high strength, high hardness, low friction coefficient, excellent wear resistance and good dimensional stability, and is widely used in various industrial fields. With the increasing demand for lightweight automobiles, polyoxymethylene has gradually been used in key components of fuel systems such as fuel pumps and oil pipelines. Automotive fuel (such as 92#, 95#, 98# gasoline and diesel) is a hydrocarbon mixture refined from petroleum through a series of chemical and physical processes. These fuels are usually in the form of transparent liquids. During long-term use, automotive fuels will penetrate into polyoxymethylene parts and cause corrosion. Under harsh conditions of use, it can cause brittle cracking of polyoxymethylene parts and eventually lead to component failure. Therefore, improving the fuel resistance of polyoxymethylene is critical to its long-term service performance.
[0003] Not only that, automotive fuels often contain acidic substances, which can also corrode polyformaldehyde parts. The polyformaldehyde products produced by existing polyformaldehyde industrial production equipment are in contact with fuel or acidic media for a long time, and their fuel resistance retention rate and acid resistance retention rate will be greatly reduced to below 50%, which seriously affects the application field, especially in the application of automotive fuel transportation or storage products. Therefore, while improving the fuel resistance of polyformaldehyde, its acid resistance must also be improved. For polyformaldehyde, acid-absorbing antacids are generally divided into metal stearates, hydrocalumite, alkali metal oxides, etc. In essence, they are an acid neutralizer that can produce a neutralization reaction with the acidic substances in automotive fuels, and improve the acid resistance of polyformaldehyde parts to a certain extent. However, some antacids will cause many problems when used alone, such as general fuel resistance, affecting the thermal stability of polyformaldehyde parts, causing severe yellowing, etc., which makes it difficult to meet the use requirements of polyformaldehyde parts in fuel systems. Summary of the invention
[0004] The main purpose of the present application is to provide a polyoxymethylene composition material and a preparation method thereof, so as to solve the problems of poor fuel resistance and poor acid resistance of polyoxymethylene materials in the prior art.
[0005] In order to achieve the above object, according to one aspect of the present application, a polyoxymethylene composition material is provided, comprising the following raw materials in parts by weight:
[0006]
[0007]
[0008] The composite acid-absorbing antacid is a compound of stearate, metal oxide and hydrated magnesium-aluminum inorganic salt; the molecular formula of hydrated magnesium-aluminum inorganic salt is Mg 1-x Al x (OH)2A n- x / n ·mH2O.
[0009] Furthermore, the weight ratio of stearate, metal oxide and hydrated magnesium aluminum inorganic salt is (5-2):(5-2):(2-1).
[0010] Furthermore, the particle size of the metal oxide and / or hydrated magnesium aluminum inorganic salt is less than or equal to 5 μm.
[0011] Furthermore, the stearate is selected from one or more of magnesium stearate, zinc stearate and calcium stearate.
[0012] Furthermore, the metal oxide is selected from one or more of magnesium oxide, zinc oxide and calcium oxide.
[0013] Furthermore, Mg 1-x Al x (OH)2A n- x / n A in mH2O n- Select from NO 3- 、CO3 2- 、SO4 2- , Cl - One or more of .
[0014] Furthermore, Mg 1-x Al x (OH)2A n- x / n ·mH2O is selected from Mg6Al2(OH) 16 CO3·4H2O、Mg6Al2(OH) 16 SO4·4H2O、Mg6Al2(OH) 16 (NO3)2·4H2O、Mg6A l2 (OH) 16 Cl2·4H2O.
[0015] Furthermore, the copolymer polyoxymethylene resin is copolymerized by trioxymethylene and dioxolane, and the weight percentage of dioxolane is 1.5-5.0%.
[0016] Furthermore, the melt index of the copolymer polyoxymethylene resin is 1.0 to 550.0 g / 10 min, and the unstable end group content thereof is less than or equal to 9000 mg / kg.
[0017] Furthermore, the anti-penetration agent is vinyl polyethylene glycol ether; preferably, the molecular weight of the vinyl polyethylene glycol ether is 1000 to 100000 g / mol.
[0018] Furthermore, the composite antioxidant is composed of antioxidant A, antioxidant B and antioxidant C; the weight ratio of antioxidant A, antioxidant B and antioxidant C is (1-2):1:(0.5-2);
[0019] Wherein, the antioxidant A is triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate;
[0020] Antioxidant B is N,N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate or n-octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate;
[0021] The antioxidant C is selected from tris(2,4-di-tert-butylphenyl)phosphite, dioctadecyl pentaerythritol diphosphite or bis(2,4-di-tert-butylphenol)pentaerythritol diphosphite.
[0022] Furthermore, the composite antioxidant is selected from triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / N,N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine / tris(2,4-di-tert-butylphenyl) phosphite, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol / tris(2,4-di-tert-butylphenyl) phosphite tert-butylphenyl) ester, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / N,N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine / dioctadecyl pentaerythritol diphosphite, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / N,N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine / bis(2,4-di-tert-butylphenol) Pentaerythritol diphosphite, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester / tris(2,4-di-tert-butylphenyl) phosphite, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester / dioctadecyl pentaerythritol diphosphite, triethylene glycol bis-β -(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester / bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite and one or more of triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester / bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite.
[0023] Furthermore, the formaldehyde absorbent is melamine and / or a derivative of melamine.
[0024] Furthermore, the macromolecular formaldehyde absorbent is a copolyamide resin containing hydrazide end groups, which is in powder form, has a particle size of less than or equal to 55 μm, and a melting point of greater than or equal to 140° C.
[0025] Furthermore, the lubricant is N,N-ethylene bisstearamide and / or glyceryl monostearate.
[0026] Furthermore, the crystal nucleating agent is talc and / or fumed silica.
[0027] Furthermore, the particle size of talc is less than or equal to 5 μm, and the particle size of fumed silica is less than or equal to 40 nm.
[0028] According to the second aspect of the present application, a method for preparing the above-mentioned polyoxymethylene composition material is provided, comprising the following steps:
[0029] Step S1: obtaining various raw materials according to the formula, mixing them to form a mixed material;
[0030] Step S2: Melting, mixing and granulating the mixed material to obtain a polyoxymethylene composite material.
[0031] Furthermore, the melting temperature is 170-245°C.
[0032] Furthermore, the operation process of step 2 is carried out in a twin-screw extruder, the screw speed is 20-600r / min, the aspect ratio of the twin screw is (25-70):1, and the vacuum degree of each exhaust section of the twin-screw extruder is ≤-0.07MPa.
[0033] By applying the technical solution of the present application, a polyoxymethylene composition material and a preparation method thereof are provided. The fuel-resistant polyoxymethylene composition has significantly better fuel and acid corrosion resistance than the current common polyoxymethylene composition, and has better thermal stability and hue, remaining in the white or light yellow phase; the fuel-resistant polyoxymethylene composition prepared by the present application has a fuel resistance retention rate and an alkali resistance retention rate of up to 80%, which is suitable for preparing automobile fuel system products and components, and can be used in occasions with high requirements for fuel resistance, acid resistance and thermal stability. The preparation method of the fuel-resistant polyoxymethylene composition provided by the present application is simple to operate and can be easily applied industrially. DETAILED DESCRIPTION
[0034] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below in conjunction with the embodiments.
[0035] The polyoxymethylene products produced by the existing polyoxymethylene industrial production equipment are in contact with fuel or acidic media for a long time, and their fuel resistance retention rate and acid resistance retention rate will be greatly reduced to below 50%, which seriously affects the application field, especially the application in automobile fuel transportation or storage products.
[0036] According to one aspect of the present application, a polyoxymethylene composite material is provided, comprising the following raw materials in parts by weight:
[0037]
[0038] Among them, the composite acid-absorbing antacid is stearate, metal oxide and Mg 1-x Al x (OH)2A n- x / n ·MHO compound; Mg 1-x Al x (OH)2An- x / n ·mH2O is hydrated magnesium aluminum inorganic salt, A n- It is an n-valent anion.
[0039] In the long-term research process, the present application found that the compounding of the above-mentioned several specific acid-absorbing antacids can greatly improve the fuel and acid resistance of polyoxymethylene products. At the same time, it is further confirmed that the compounding of acid-absorbing antacids and anti-penetration agents has a good synergistic effect, which can effectively improve the thermal stability of polyoxymethylene and obtain a good color while improving the fuel and acid resistance of polyoxymethylene.
[0040] The fuel-resistant polyformaldehyde composite material selected in this application refers to a high-end polyformaldehyde product that can be converted online on a 10,000-ton polyformaldehyde production device. This product is different from general-purpose polyformaldehyde or other polyformaldehyde products. Its notable feature is its excellent fuel resistance and acid corrosion resistance.
[0041] The above-mentioned fuel-resistant polyformaldehyde composition material of the present application has significantly better fuel resistance and acid corrosion resistance than the current ordinary polyformaldehyde composition, and has good thermal stability and hue, remaining in a white phase or a light yellow phase. Its fuel resistance retention rate and alkali resistance retention rate can reach 80%, and it is suitable for the preparation of automobile fuel system products and components, and can be used in occasions with high requirements for fuel resistance, acid resistance and thermal stability.
[0042] In some embodiments, stearate, metal oxide and Mg 1-x Al x (OH)2A n- x / n The weight ratio of mH2O is (5-2): (5-2): (2-1); for example, (5, 4, 3, 2, 1, or any range between two values): (5, 4, 3, 2, 1, or any range between two values): (1 or 2). 1-x Al x (OH)2A n- x / n When mH2O is mixed in the above specific proportion, the three play a good synergistic role, which can further improve the acid corrosion resistance and fuel resistance of the material and improve the overall effect.
[0043] In some embodiments, metal oxides and / or Mg 1-x Al x (OH)2A n- x / n The particle size of mH2O is less than or equal to 5 μm. In the present application, the particle sizes of the two substances are controlled to be less than 5 μm, so that they can be fully and evenly mixed with stearate to give full play to better anti-acid effect.
[0044] In some embodiments, the stearate is selected from one or more of magnesium stearate, zinc stearate and calcium stearate. The three stearates selected in this application all have good acid resistance, good chemical stability and safety.
[0045] In some embodiments, the metal oxide is selected from one or more of magnesium oxide, zinc oxide and calcium oxide. The three metal oxides selected in this application all have good acid resistance, and zinc oxide also has a certain antibacterial effect.
[0046] In some embodiments, Mg 1-x Al x (OH)2A n- x / n A in mH2O n- Select from NO 3- 、CO3 2- 、SO4 2- , Cl - One or more of; preferably, Mg 1-x Al x (OH)2A n- x / n ·mH2O is selected from Mg6Al2(OH) 16 CO3·4H2O、Mg6Al2(OH) 16 SO4·4H2O、Mg6Al2(OH) 16 (NO3)2·4H2O、Mg6A l2 (OH) 16 Cl2·4H2O.
[0047] The above-mentioned substance selected in the present application is a layered double-layer metal hydroxide, also known as magnesium aluminum hydroxide hydrotalcite (LDHs), in which divalent and trivalent metal cations are surrounded by hydroxide ions to form a layered structure, and its alkaline sites can be reacted and grafted with other compounds. It is an acid-resistant material with good acid resistance, which is due to its layered structure and adjustable acidity and alkalinity; it has good thermal stability, is flame retardant, and is environmentally friendly.
[0048] In some embodiments, the copolymerized polyoxymethylene resin is copolymerized with trioxymethylene and dioxolane, and the weight percentage of dioxolane is 1.5-5.0%; the melt index of the copolymerized polyoxymethylene resin is 1.0-550.0g / 10min, and the unstable end group content is less than or equal to 9000mg / kg. The present application adopts the above-mentioned two materials in the above proportion to obtain the polyoxymethylene resin by copolymerization, wherein the addition of dioxolane in a characteristic proportion can increase the thermal decomposition temperature of the hot polyoxymethylene, so that the polyoxymethylene has better effects in terms of thermal stability, crystallinity, mechanical properties, etc., and is an engineering plastic with excellent performance.
[0049] In some embodiments, the anti-permeation agent is vinyl polyethylene glycol ether; preferably, the molecular weight of the vinyl polyethylene glycol ether is 1000-100000 g / mol.
[0050] This application uses vinyl polyglycol ether as an anti-penetration agent, which can reduce the porosity of the material, improve the density of the material, effectively organize the penetration of liquids such as fuel, and also reduce the diffusion coefficient in the copolymerized polyoxymethylene material. It can form a physical barrier on the surface of the material, reduce the penetration process, reduce the penetration of corrosive media, improve the durability of the material, and extend the service life of the material.
[0051] The stearates, metal oxides and Mg selected in this application 1-x Al x (OH)2A n- x / n The mH2O compound and the above-mentioned vinyl polyglycol ether anti-penetration agent have a good system effect, which can synergistically improve the acid corrosion resistance and fuel resistance of polyoxymethylene.
[0052] In some embodiments, the composite antioxidant is composed of antioxidant A, antioxidant B and antioxidant C; the weight ratio of antioxidant A, antioxidant B and antioxidant C is (1-2):1:(0.5-2);
[0053] Wherein, the antioxidant A is triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate;
[0054] Antioxidant B is N,N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate or n-octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate;
[0055] The antioxidant C is selected from tris(2,4-di-tert-butylphenyl)phosphite, dioctadecyl pentaerythritol diphosphite or bis(2,4-di-tert-butylphenol)pentaerythritol diphosphite.
[0056] Furthermore, the composite antioxidant is selected from triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / N,N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine / tris(2,4-di-tert-butylphenyl) phosphite, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol / tris(2,4-di-tert-butylphenyl) phosphite tert-butylphenyl) ester, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / N,N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine / dioctadecyl pentaerythritol diphosphite, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / N,N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine / bis(2,4-di-tert-butylphenol) Pentaerythritol diphosphite, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester / tris(2,4-di-tert-butylphenyl) phosphite, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester / dioctadecyl pentaerythritol diphosphite, triethylene glycol bis-β -(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester / bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite and one or more of triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester / bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite.
[0057] The above three antioxidants selected in this application have synergistic antioxidant effects. These three compounds each have different antioxidant mechanisms, and can produce a synergistic effect when used in combination, thereby more effectively preventing the oxidative degradation of the material. Antioxidant B, as an amine antioxidant, can react with free radicals to prevent chain oxidation reactions; Antioxidant A has good compatibility with polymer resins, high antioxidant efficiency, and can improve thermal stability and light stability; Antioxidant C, as a phosphate antioxidant, can effectively capture free radicals, prevent oxidation chain reactions, and enhance the overall antioxidant performance.
[0058] In some embodiments, the formaldehyde absorber is melamine and / or a derivative of melamine.
[0059] The present application adopts melamine as a formaldehyde absorber, which can not only improve water resistance, but also effectively reduce the free formaldehyde content, and also improve the thermal stability and mechanical properties of the material.
[0060] In some embodiments, the macromolecular formaldehyde absorbent is a copolyamide resin containing hydrazide end groups, which is in powder form, has a particle size of less than or equal to 55 μm, and a melting point of greater than or equal to 140° C.
[0061] The present application selects the above copolyamide resin, especially the presence of hydrazide groups, which can effectively react with formaldehyde to absorb macromolecular formaldehyde. The copolyamide resin has a high molecular weight, good thermal stability, and is not easy to be oxidized during processing, making it more stable and effective as a formaldehyde absorbent. The present application uses melamine and a copolyamide resin containing hydrazide end groups as a formaldehyde absorbent, which can effectively improve the thermal stability of polyoxymethylene.
[0062] In some embodiments, the lubricant is N,N-ethylene bis stearamide and / or glyceryl monostearate. The present application selects these two lubricants, both of which have good lubrication effects, can reduce friction, improve processing efficiency, and improve product surface quality and physical properties.
[0063] In some embodiments, the crystal nucleating agent is talc and / or fumed silica; wherein the particle size of the talc is less than or equal to 5 μm, and the particle size of the fumed silica is less than or equal to 40 nm.
[0064] The present application selects the materials with the above characteristics as crystallization nucleating agents, which can promote the nucleation and crystallization of polyformaldehyde, control the crystal morphology of the polymer, accelerate the crystallization rate, make the crystallization more uniform, reduce the internal stress concentration of the material, and improve the overall mechanical properties of the polymer.
[0065] According to the second aspect of the present application, a method for preparing the above-mentioned polyoxymethylene composition material is provided, comprising the following steps:
[0066] Step S1: obtaining various raw materials according to the formula, mixing them to form a mixed material;
[0067] Step S2: Melting, mixing and granulating the mixed material to obtain a polyoxymethylene composite material.
[0068] In some embodiments, the melting temperature is 170-245°C.
[0069] The operation process of step 2 is carried out in a twin-screw extruder, the screw speed is 20-600r / min, the aspect ratio of the twin screw is (25-70):1, and the vacuum degree of each exhaust section of the twin-screw extruder is ≤-0.07MPa.
[0070] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0071] The copolymer formaldehyde resin used in the examples of the present application is produced by Ningxia Coal Industry Company of the State Energy Group; other raw materials can be purchased commercially.
[0072] Example 1
[0073] The material ratio of the polyoxymethylene composition is as follows:
[0074] Copolymer polyoxymethylene resin: 100 parts, melt index 9.0 g / 10 min, dioxolane monomer weight content 1.5%, unstable end group content 1000 mg / kg;
[0075] Formaldehyde absorbent: 0.02 parts, melamine or melamine derivatives;
[0076] Macromolecular formaldehyde absorbent: 0.02 parts, copolyamide resin containing hydrazide end groups, powder, particle size 10 μm;
[0077] Composite antioxidant: 0.20 parts, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / N, N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine / dioctadecyl pentaerythritol diphosphite, the weight ratio of the three components is 1:1:1;
[0078] Composite acid-absorbing antacid: 0.1 part, magnesium stearate / magnesium oxide / Mg6Al2(OH) 16 CO3·4H2O, the ratio of the three is 5:5:2, magnesium oxide and / Mg6Al2(OH) 16 The particle size of CO3·4H2O is 2 μm;
[0079] Anti-penetration agent: 0.20 parts, vinyl polyethylene glycol ether, molecular weight 1000g / mol;
[0080] Lubricant: 0.05 parts, N,N-ethylene bisstearamide;
[0081] Crystal nucleating agent: 0.02 parts, talcum powder, particle size 5 μm;
[0082] The above materials are added into a high-speed mixer for premixing, and then melted, mixed, extruded and granulated by a twin-screw extruder to obtain a polyoxymethylene composite material; wherein the processing temperature is 170°C and the screw speed is 600r / min. The twin-screw extruder used is a large-capacity evaporation (multi-stage exhaust) devolatilization twin-screw unit with a length-to-diameter ratio of 50:1. During operation, the vacuum degree of each exhaust section of the twin-screw extruder is -0.07MPa.
[0083] Example 2
[0084] The polyoxymethylene composition ratio is as follows:
[0085] Copolymer polyoxymethylene resin: 100 parts, melt index 9.0 g / 10 min, dioxolane monomer weight content 5%, unstable terminal group content 1000 mg / kg;
[0086] Formaldehyde absorber: 1 part, melamine or melamine derivatives;
[0087] Macromolecular formaldehyde absorbent: 0.02 parts, copolyamide resin containing hydrazide end groups, powder, particle size 10 μm;
[0088] Composite antioxidant: 0.20 parts, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] / tris(2,4-di-tert-butylphenyl) phosphite, the weight ratio of the three components is 1:1:1;
[0089] Composite acid-absorbing antacid: 5 parts, zinc stearate / zinc oxide / Mg6Al2(OH) 16 SO4·4H2O, the ratio of the three is 2:2:1, zinc oxide and Mg6Al2(OH) 16 The particle size of SO4·4H2O is 2 μm;
[0090] Anti-penetration agent: 5 parts, vinyl polyethylene glycol ether, molecular weight 100000 g / mol;
[0091] Lubricant: 0.05 parts, glyceryl monostearate;
[0092] Crystal nucleating agent: 0.02 parts, fumed silica / talc, the weight ratio of the two components is 1:1;
[0093] The above materials are added into a high-speed mixer for premixing, and then melted, mixed, extruded and granulated by a twin-screw extruder to obtain a polyoxymethylene composite material; wherein the processing temperature is 200°C and the screw speed is 600r / min. The twin-screw extruder used is a large-capacity evaporation (multi-stage exhaust) devolatilization twin-screw unit with a length-to-diameter ratio of 50:1. During operation, the vacuum degree of each exhaust section of the twin-screw extruder is -0.07MPa.
[0094] Example 3
[0095] The polyoxymethylene composition ratio is as follows:
[0096] Copolymer polyoxymethylene resin: 100 parts, melt index 9.0 g / 10 min, dioxolane monomer weight content 1.5%, unstable end group content 1000 mg / kg;
[0097] Formaldehyde absorbent: 0.02 parts, melamine or melamine derivatives;
[0098] Macromolecular formaldehyde absorbent: 1 part, copolyamide resin containing hydrazide end groups, powder, particle size 10 μm;
[0099] Composite antioxidant: 0.20 parts, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / N, N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine / dioctadecyl pentaerythritol diphosphite, the weight ratio of the three components is 1:1:2;
[0100] Composite acid-absorbing antacid: 0.20 parts, calcium stearate / calcium oxide / Mg6Al2(OH) 16 (NO3)2·4H2O, the ratio of the three is 4:4:1, calcium oxide and Mg6Al2(OH) 16 The particle size of (NO3)2·4H2O is 2 μm;
[0101] Anti-penetration agent: 0.50 parts, vinyl polyethylene glycol ether, molecular weight 2000g / mol;
[0102] Lubricant: 0.05 parts, N,N-ethylene bisstearamide;
[0103] Crystal nucleating agent: 0.02 parts, talcum powder, particle size 5 μm;
[0104] The above materials are added into a high-speed mixer for premixing, and then melted, mixed, extruded and granulated by a twin-screw extruder to obtain a polyoxymethylene composite material; wherein the processing temperature is 190°C and the screw speed is 600r / min. The twin-screw extruder used is a large-capacity evaporation (multi-stage exhaust) devolatilization twin-screw unit with a length-to-diameter ratio of 50:1. During operation, the vacuum degree of each exhaust section of the twin-screw extruder is -0.07MPa.
[0105] Example 4
[0106] The polyoxymethylene composition ratio is as follows:
[0107] Copolymer polyoxymethylene resin: 100 parts, melt index 9.0 g / 10 min, dioxolane monomer weight content 1.5%, unstable end group content 1000 mg / kg;
[0108] Formaldehyde absorbent: 0.02 parts, melamine or melamine derivatives;
[0109] Macromolecular formaldehyde absorbent: 0.02 parts, copolyamide resin containing hydrazide end groups, powder, particle size 10 μm;
[0110] Composite antioxidant: 1 part, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / N, N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine / bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite, the weight ratio of the three components is 2:1:0.5;
[0111] Compound acid-absorbing antacid: 2 parts, magnesium stearate / zinc oxide / Mg6Al2(OH) 16 Cl2·4H2O, the ratio of the three is 3:3:2, zinc oxide / Mg6Al2(OH) 16 The particle size of Cl2·4H2O is 1 μm;
[0112] Anti-penetration agent: 2 parts, vinyl polyethylene glycol ether, molecular weight 4000g / mol;
[0113] Lubricant: 0.05 parts, glyceryl monostearate;
[0114] Crystal nucleating agent: 0.02 parts, fumed silica, particle size 20 nm;
[0115] The above materials are added into a high-speed mixer for premixing, and then melted, mixed, extruded and granulated by a twin-screw extruder to obtain a polyoxymethylene composition; wherein the processing temperature is 210°C and the screw speed is 600r / min. The twin-screw extruder used is a large-capacity evaporation (multi-stage exhaust) devolatilization twin-screw unit with a length-to-diameter ratio of 50:1. During operation, the vacuum degree of each exhaust section of the twin-screw extruder is -0.07MPa.
[0116] Example 5
[0117] The polyoxymethylene composition ratio is as follows:
[0118] Copolymer polyoxymethylene resin: 100 parts, melt index 9.0 g / 10 min, dioxolane monomer weight content 1.5%, unstable end group content 1000 mg / kg;
[0119] Formaldehyde absorbent: 0.02 parts, melamine or melamine derivatives;
[0120] Macromolecular formaldehyde absorbent: 0.02 parts, copolyamide resin containing hydrazide end groups, powder, particle size 10 μm;
[0121] Composite antioxidant: 0.20 parts, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate / tris(2,4-di-tert-butylphenyl) phosphite, the weight ratio of the three components is 1:1:1;
[0122] Compound acid-absorbing antacid: 3 parts, zinc stearate / calcium oxide / Mg6Al2(OH) 16 CO3·4H2O, the ratio of the three is 5:3:2, calcium oxide and Mg6Al2(OH) 16 The particle size of CO3·4H2O is 1 μm;
[0123] Anti-penetration agent: 3 parts, vinyl polyethylene glycol ether, molecular weight 6000g / mol;
[0124] Lubricant: 0.05 parts, N,N-ethylene bisstearamide;
[0125] Crystal nucleating agent: 0.02 parts, talcum powder, particle size 5 μm;
[0126] The above materials are added into a high-speed mixer for premixing, and then melted, mixed, extruded and granulated by a twin-screw extruder to obtain a polyoxymethylene composition; wherein the processing temperature is 215°C and the screw speed is 600r / min. The twin-screw extruder used is a large-capacity evaporation (multi-stage exhaust) devolatilization twin-screw unit with a length-to-diameter ratio of 50:1. During operation, the vacuum degree of each exhaust section of the twin-screw extruder is -0.07MPa.
[0127] Example 6
[0128] The polyoxymethylene composition ratio is as follows:
[0129] Copolymer polyoxymethylene resin: 100 parts, melt index 9.0 g / 10 min, dioxolane monomer weight content 1.5%, unstable end group content 1000 mg / kg;
[0130] Formaldehyde absorbent: 0.02 parts, melamine or melamine derivatives;
[0131] Macromolecular formaldehyde absorbent: 0.02 parts, copolyamide resin containing hydrazide end groups, powder, particle size 10 μm;
[0132] Composite antioxidant: 0.20 parts, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate / dioctadecyl pentaerythritol diphosphite, the weight ratio of the three components is 1:1:1;
[0133] Compound acid-absorbing antacid: 0.3 parts, calcium stearate / magnesium oxide / Mg6Al2(OH) 16 SO4·4H2O, the ratio of the three is 3:4:1, magnesium oxide and Mg6Al2(OH) 16 The particle size of SO4·4H2O is 1 μm;
[0134] Anti-penetration agent: 0.3 parts, vinyl polyethylene glycol ether, molecular weight 8000g / mol;
[0135] Lubricant: 0.05 parts, N,N-ethylene bisstearamide / glyceryl monostearate, the weight ratio of the two components is 1:1;
[0136] Crystal nucleating agent: 0.02 parts, fumed silica, particle size 20 nm;
[0137] The above materials are added into a high-speed mixer for premixing, and then melted, mixed, extruded and granulated by a twin-screw extruder to obtain a polyoxymethylene composition; wherein the processing temperature is 185°C and the screw speed is 600r / min. The twin-screw extruder used is a large-capacity evaporation (multi-stage exhaust) devolatilization twin-screw unit with a length-to-diameter ratio of 50:1. During operation, the vacuum degree of each exhaust section of the twin-screw extruder is -0.07MPa.
[0138] Example 7
[0139] The polyoxymethylene composition ratio is as follows:
[0140] Copolymer polyoxymethylene resin: 100 parts, melt index 9.0 g / 10 min, dioxolane monomer weight content 1.5%, unstable end group content 1000 mg / kg;
[0141] Formaldehyde absorbent: 0.02 parts, melamine or melamine derivatives;
[0142] Macromolecular formaldehyde absorbent: 0.02 parts, copolyamide resin containing hydrazide end groups, powder, particle size 10 μm;
[0143] Composite antioxidant: 0.20 parts, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate / bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite, the weight ratio of the three components is 1:1:1;
[0144] Composite acid-absorbing antacid: 0.4 parts, calcium stearate / zinc oxide / Mg6Al2(OH) 16 (NO3)2·4H2O, the ratio of the three is 4:3:2, zinc oxide and Mg6Al2(OH) 16 The particle size of (NO3)2·4H2O is 2 μm;
[0145] Anti-penetration agent: 0.4 parts, vinyl polyethylene glycol ether, molecular weight 10000g / mol;
[0146] Lubricant: 1 part, N,N-ethylene bisstearamide;
[0147] Crystal nucleating agent: 0.02 parts, talcum powder, particle size 5 μm;
[0148] The above materials are added into a high-speed mixer for premixing, and then melted, mixed, extruded and granulated by a twin-screw extruder to obtain a polyoxymethylene composition; wherein the processing temperature is 195°C and the screw speed is 600r / min. The twin-screw extruder used is a large-capacity evaporation (multi-stage exhaust) devolatilization twin-screw unit with a length-to-diameter ratio of 50:1. During operation, the vacuum degree of each exhaust section of the twin-screw extruder is -0.07MPa.
[0149] Example 8
[0150] The polyoxymethylene composition ratio is as follows:
[0151] Copolymer polyoxymethylene resin: 100 parts, melt index 9.0 g / 10 min, dioxolane monomer weight content 1.5%, unstable end group content 1000 mg / kg;
[0152] Formaldehyde absorbent: 0.02 parts, melamine or melamine derivatives;
[0153] Macromolecular formaldehyde absorbent: 0.02 parts, copolyamide resin containing hydrazide end groups, powder, particle size 10 μm;
[0154] Composite antioxidant: 0.20 parts, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate / bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite, the weight ratio of the three components is 1:1:1;
[0155] Composite acid-absorbing antacid: 0.7 parts, zinc stearate / magnesium oxide / Mg6Al2(OH) 16 Cl2·4H2O, the ratio of the three is 5:2:1, magnesium oxide and Mg6Al2(OH) 16 The particle size of Cl2·4H2O is 2 μm;
[0156] Anti-penetration agent: 0.7 parts, vinyl polyethylene glycol ether, molecular weight 12000g / mol;
[0157] Lubricant: 0.05 parts, glyceryl monostearate;
[0158] Crystal nucleating agent: 0.5 parts, fumed silica, particle size 20 nm;
[0159] The above materials are added into a high-speed mixer for premixing, and then melted, mixed, extruded and granulated by a twin-screw extruder to obtain a polyoxymethylene composition; wherein the processing temperature is 200°C and the screw speed is 600r / min. The twin-screw extruder used is a large-capacity evaporation (multi-stage exhaust) devolatilization twin-screw unit with a length-to-diameter ratio of 50:1. During operation, the vacuum degree of each exhaust section of the twin-screw extruder is -0.07MPa.
[0160] Example 9
[0161] The polyoxymethylene composition ratio is as follows:
[0162] Copolymer polyoxymethylene resin: 100 parts, melt index 9.0 g / 10 min, dioxolane monomer weight content 1.5%, unstable end group content 1000 mg / kg;
[0163] Formaldehyde absorber: 1 part, melamine or melamine derivatives;
[0164] Macromolecular formaldehyde absorbent: 1 part, copolyamide resin containing hydrazide end groups, powder, particle size 10 μm;
[0165] Composite antioxidant: 1 part, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate / bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite, the weight ratio of the three components is 1:1:1;
[0166] Composite acid-absorbing antacid: 0.9 parts, magnesium stearate / calcium oxide / Mg6Al2(OH) 16 (NO3)2·4H2O, the ratio of the three is 3:2:2, calcium oxide and Mg6Al2(OH) 16 The particle size of (NO3)2·4H2O is 2 μm;
[0167] Anti-penetration agent: 0.9 parts, vinyl polyethylene glycol ether, molecular weight 14000g / mol;
[0168] Lubricant: 1 part, N,N-ethylene bisstearamide;
[0169] Crystal nucleating agent: 0.5 parts, talcum powder, particle size 5 μm;
[0170] The above materials are added into a high-speed mixer for premixing, and then melted, mixed, extruded and granulated by a twin-screw extruder to obtain a polyoxymethylene composition; wherein the processing temperature is 230°C and the screw speed is 600r / min. The twin-screw extruder used is a large-capacity evaporation (multi-stage exhaust) devolatilization twin-screw unit with a length-to-diameter ratio of 50:1. During operation, the vacuum degree of each exhaust section of the twin-screw extruder is -0.07MPa.
[0171] Comparative Example 1
[0172] The polyoxymethylene composition ratio is as follows:
[0173] Copolymer polyoxymethylene resin: 100 parts, melt index 9.0 g / 10 min, dioxolane monomer weight content 1.5%, unstable end group content 1000 mg / kg;
[0174] Formaldehyde absorbent: 0.02 parts, melamine or melamine derivatives;
[0175] Macromolecular formaldehyde absorbent: 0.02 parts, copolyamide resin containing hydrazide end groups, powder, particle size 10 μm;
[0176] Composite antioxidant: 0.2 parts, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / N, N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine / dioctadecyl pentaerythritol diphosphite, the weight ratio of the three components is 1:1:1;
[0177] Composite acid-absorbing antacid: 0.1 part, magnesium oxide / Mg6Al2(OH) 16 CO3·4H2O, the ratio of the two is 5:2, magnesium oxide and Mg6Al2(OH) 16 The particle size of CO3·4H2O is 2 μm;
[0178] Anti-penetration agent: 0.20 parts, vinyl polyethylene glycol ether, molecular weight 1000g / mol;
[0179] Lubricant: 0.05 parts, N,N-ethylene bisstearamide;
[0180] Crystal nucleating agent: 0.02 parts, talcum powder, particle size 5 μm;
[0181] The above materials are added into a high-speed mixer for premixing, and then melted, mixed, extruded and granulated by a twin-screw extruder to obtain a polyoxymethylene composition; wherein the processing temperature is 180°C and the screw speed is 600r / min. The twin-screw extruder used is a large-capacity evaporation (multi-stage exhaust) devolatilization twin-screw unit with a length-to-diameter ratio of 50:1. During operation, the vacuum degree of each exhaust section of the twin-screw extruder is -0.07MPa.
[0182] Comparative Example 2
[0183] The polyoxymethylene composition ratio is as follows:
[0184] Copolymer polyoxymethylene resin: 100 parts, melt index 9.0 g / 10 min, dioxolane monomer weight content 1.5%, unstable end group content 1000 mg / kg;
[0185] Formaldehyde absorbent: 0.02 parts, melamine or melamine derivatives;
[0186] Macromolecular formaldehyde absorbent: 0.02 parts, copolyamide resin containing hydrazide end groups, powder, particle size 10 μm;
[0187] Composite antioxidant: 0.20 parts, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate / dioctadecyl pentaerythritol diphosphite, the weight ratio of the three components is 1:1:1;
[0188] Composite acid-absorbing antacid: 5 parts, zinc stearate / Mg6Al2(OH) 16 SO4·4H2O, the ratio of the two is 2:1, Mg6Al2(OH) 16 The particle size of SO4·4H2O is 2 μm;
[0189] Anti-penetration agent: 5 parts, vinyl polyethylene glycol ether, molecular weight 100000 g / mol;
[0190] Lubricant: 0.05 parts, N,N-ethylene bisstearamide / glyceryl monostearate, the weight ratio of the two components is 1:1;
[0191] Crystal nucleating agent: 0.02 parts, fumed silica, particle size 20 nm;
[0192] The above materials are added into a high-speed mixer for premixing, and then melted, mixed, extruded and granulated by a twin-screw extruder to obtain a polyoxymethylene composition; wherein the processing temperature is 220°C and the screw speed is 600r / min. The twin-screw extruder used is a large-capacity evaporation (multi-stage exhaust) devolatilization twin-screw unit with a length-to-diameter ratio of 50:1. During operation, the vacuum degree of each exhaust section of the twin-screw extruder is -0.07MPa.
[0193] Comparative Example 2
[0194] The polyoxymethylene composition ratio is as follows:
[0195] Copolymer polyoxymethylene resin: 100 parts, melt index 9.0 g / 10 min, dioxolane monomer weight content 1.5%, unstable end group content 1000 mg / kg;
[0196] Formaldehyde absorbent: 0.02 parts, melamine or melamine derivatives;
[0197] Macromolecular formaldehyde absorbent: 1 part, copolyamide resin containing hydrazide end groups, powder, particle size 10 μm;
[0198] Composite antioxidant: 0.20 parts, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / N, N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine / dioctadecyl pentaerythritol diphosphite, the weight ratio of the three components is 1:1:2;
[0199] Composite acid-absorbing antacid: 0.20 parts, calcium stearate / calcium oxide, the ratio of the two is 4:4, and the particle size of calcium oxide is 2μm;
[0200] Anti-penetration agent: 0.50 parts, vinyl polyethylene glycol ether, molecular weight 2000g / mol;
[0201] Lubricant: 0.05 parts, N,N-ethylene bisstearamide;
[0202] Crystal nucleating agent: 0.02 parts, talcum powder, particle size 5 μm;
[0203] The above materials are added into a high-speed mixer for premixing, and then melted, mixed, extruded and granulated by a twin-screw extruder to obtain a polyoxymethylene composition; wherein the processing temperature is 200°C and the screw speed is 600r / min. The twin-screw extruder used is a large-capacity evaporation (multi-stage exhaust) devolatilization twin-screw unit with a length-to-diameter ratio of 50:1. During operation, the vacuum degree of each exhaust section of the twin-screw extruder is -0.07MPa.
[0204] Comparative Example 3
[0205] The polyoxymethylene composition ratio is as follows:
[0206] Copolymer polyoxymethylene resin: 100 parts, melt index 9.0 g / 10 min, dioxolane monomer weight content 1.5%, unstable end group content 1000 mg / kg;
[0207] Formaldehyde absorbent: 0.02 parts, melamine or melamine derivatives;
[0208] Macromolecular formaldehyde absorbent: 1 part, copolyamide resin containing hydrazide end groups, powder, particle size 10 μm;
[0209] Composite antioxidant: 0.20 parts, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / N, N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine / dioctadecyl pentaerythritol diphosphite, the weight ratio of the three components is 1:1:2;
[0210] Composite acid-absorbing antacid: 0.20 parts, calcium stearate / calcium oxide, the ratio of the two is 4:4, and the particle size of calcium oxide is 2μm;
[0211] Anti-penetration agent: 0.50 parts, vinyl polyethylene glycol ether, molecular weight 2000g / mol;
[0212] Lubricant: 0.05 parts, N,N-ethylene bisstearamide;
[0213] Crystal nucleating agent: 0.02 parts, talcum powder, particle size 5 μm;
[0214] The above materials are added into a high-speed mixer for premixing, and then melted, mixed, extruded and granulated by a twin-screw extruder to obtain a polyoxymethylene composition; wherein the processing temperature is 170-240°C, and the screw speed is 600r / min. The twin-screw extruder used is a large-capacity evaporation (multi-stage exhaust) devolatilization twin-screw unit, with a length-to-diameter ratio of 50:1, and the vacuum degree of each exhaust section of the twin-screw extruder during operation is -0.07MPa.
[0215] Comparative Example 4
[0216] The polyoxymethylene composition ratio is as follows:
[0217] Copolymer polyoxymethylene resin: 100 parts, melt index 9.0 g / 10 min, dioxolane monomer weight content 1.5%, unstable end group content 1000 mg / kg;
[0218] Formaldehyde absorbent: 0.02 parts, melamine or melamine derivatives;
[0219] Macromolecular formaldehyde absorbent: 1 part, copolyamide resin containing hydrazide end groups, powder, particle size 10 μm;
[0220] Composite antioxidant: 0.20 parts, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / N, N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine / dioctadecyl pentaerythritol diphosphite, the weight ratio of the three components is 1:1:2;
[0221] Compound acid-absorbing antacid: 1 part, magnesium stearate;
[0222] Anti-penetration agent: 1 part, vinyl polyethylene glycol ether, molecular weight 10000g / mol;
[0223] Lubricant: 0.05 parts, N,N-ethylene bisstearamide;
[0224] Crystal nucleating agent: 0.02 parts, talcum powder, particle size 5 μm;
[0225] The above materials are added into a high-speed mixer for premixing, and then melted, mixed, extruded and granulated by a twin-screw extruder to obtain a polyoxymethylene composition; wherein the processing temperature is 200°C and the screw speed is 600r / min. The twin-screw extruder used is a large-capacity evaporation (multi-stage exhaust) devolatilization twin-screw unit with a length-to-diameter ratio of 50:1. During operation, the vacuum degree of each exhaust section of the twin-screw extruder is -0.07MPa.
[0226] Comparative Example 5
[0227] The polyoxymethylene composition ratio is as follows:
[0228] Copolymer polyoxymethylene resin: 100 parts, melt index 9.0 g / 10 min, dioxolane monomer weight content 1.5%, unstable end group content 1000 mg / kg;
[0229] Formaldehyde absorbent: 0.02 parts, melamine or melamine derivatives;
[0230] Macromolecular formaldehyde absorbent: 1 part, copolyamide resin containing hydrazide end groups, powder, particle size 10 μm;
[0231] Composite antioxidant: 0.20 parts, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / N, N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine / dioctadecyl pentaerythritol diphosphite, the weight ratio of the three components is 1:1:2;
[0232] Compound acid-absorbing antacid: 2 parts, zinc oxide, particle size 2 μm;
[0233] Anti-penetration agent: 2 parts, vinyl polyethylene glycol ether, molecular weight 12000g / mol;
[0234] Lubricant: 0.05 parts, N,N-ethylene bisstearamide;
[0235] Crystal nucleating agent: 0.02 parts, talcum powder, particle size 5 μm;
[0236] The above materials are added into a high-speed mixer for premixing, and then melted, mixed, extruded and granulated by a twin-screw extruder to obtain a polyoxymethylene composition; wherein the processing temperature is 200°C and the screw speed is 600r / min. The twin-screw extruder used is a large-capacity evaporation (multi-stage exhaust) devolatilization twin-screw unit with a length-to-diameter ratio of 50:1. During operation, the vacuum degree of each exhaust section of the twin-screw extruder is -0.07MPa.
[0237] Comparative Example 6
[0238] The polyoxymethylene composition ratio is as follows:
[0239] Copolymer polyoxymethylene resin: 100 parts, melt index 9.0 g / 10 min, dioxolane monomer weight content 1.5%, unstable end group content 1000 mg / kg;
[0240] Formaldehyde absorbent: 0.02 parts, melamine or melamine derivatives;
[0241] Macromolecular formaldehyde absorbent: 1 part, copolyamide resin containing hydrazide end groups, powder, particle size 10 μm;
[0242] Composite antioxidant: 0.20 parts, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / N, N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine / dioctadecyl pentaerythritol diphosphite, the weight ratio of the three components is 1:1:2;
[0243] Composite acid-absorbing antacid: 0.80 parts, Mg6Al2(OH) 16 Cl2·4H2O, particle size 2 μm;
[0244] Anti-penetration agent: 0.80 parts, vinyl polyethylene glycol ether, molecular weight 5000g / mol;
[0245] Lubricant: 0.05 parts, N,N-ethylene bisstearamide;
[0246] Crystal nucleating agent: 0.02 parts, talcum powder, particle size 5 μm;
[0247] The above materials are added into a high-speed mixer for premixing, and then melted, mixed, extruded and granulated by a twin-screw extruder to obtain a polyoxymethylene composition; wherein the processing temperature is 200°C and the screw speed is 600r / min. The twin-screw extruder used is a large-capacity evaporation (multi-stage exhaust) devolatilization twin-screw unit with a length-to-diameter ratio of 50:1. During operation, the vacuum degree of each exhaust section of the twin-screw extruder is -0.07MPa.
[0248] Comparative Example 7
[0249] The polyoxymethylene composition ratio is as follows:
[0250] Copolymer polyoxymethylene resin: 100 parts, melt index 9.0 g / 10 min, dioxolane monomer weight content 5%, unstable terminal group content 1000 mg / kg;
[0251] Formaldehyde absorber: 1 part, melamine or melamine derivatives;
[0252] Macromolecular formaldehyde absorbent: 0.02 parts, copolyamide resin containing hydrazide end groups, powder, particle size 10 μm;
[0253] Composite antioxidant: 0.20 parts, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] / tris(2,4-di-tert-butylphenyl) phosphite, the weight ratio of the three components is 1:1:1;
[0254] Anti-penetration agent: 0.60 parts, vinyl polyethylene glycol ether, molecular weight 7000g / mol;
[0255] Lubricant: 0.05 parts, glyceryl monostearate;
[0256] Crystal nucleating agent: 0.02 parts, fumed silica / talc, the weight ratio of the two components is 1:1;
[0257] The above materials are added into a high-speed mixer for premixing, and then melted, mixed, extruded and granulated by a twin-screw extruder to obtain a polyoxymethylene composition; wherein the processing temperature is 180°C and the screw speed is 600r / min. The twin-screw extruder used is a large-capacity evaporation (multi-stage exhaust) devolatilization twin-screw unit with a length-to-diameter ratio of 50:1. During operation, the vacuum degree of each exhaust section of the twin-screw extruder is -0.07MPa.
[0258] Comparative Example 8
[0259] The polyoxymethylene composition ratio is as follows:
[0260] Copolymer polyoxymethylene resin: 100 parts, melt index 9.0 g / 10 min, dioxolane monomer weight content 5%, unstable terminal group content 1000 mg / kg;
[0261] Formaldehyde absorber: 1 part, melamine or melamine derivatives;
[0262] Macromolecular formaldehyde absorbent: 0.02 parts, copolyamide resin containing hydrazide end groups, powder, particle size 10 μm;
[0263] Composite antioxidant: 0.20 parts, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] / tris(2,4-di-tert-butylphenyl) phosphite, the weight ratio of the three components is 1:1:1;
[0264] Composite acid-absorbing antacid: 1.20 parts, zinc stearate / magnesium oxide / Mg6Al2(OH) 16 SO4·4H2O, the ratio of the three is 2:2:2, magnesium oxide and Mg6Al2(OH) 16 The particle size of SO4·4H2O is 2 μm;
[0265] Lubricant: 0.05 parts, glyceryl monostearate;
[0266] Crystal nucleating agent: 0.02 parts, fumed silica / talc, the weight ratio of the two components is 1:1;
[0267] The above materials are added into a high-speed mixer for premixing, and then melted, mixed, extruded and granulated by a twin-screw extruder to obtain a polyoxymethylene composition; wherein the processing temperature is 200°C and the screw speed is 600r / min. The twin-screw extruder used is a large-capacity evaporation (multi-stage exhaust) devolatilization twin-screw unit with a length-to-diameter ratio of 50:1. During operation, the vacuum degree of each exhaust section of the twin-screw extruder is -0.07MPa.
[0268] Comparative Example 9
[0269] The polyoxymethylene composition ratio is as follows:
[0270] Copolymer polyoxymethylene resin: 100 parts, melt index 9.0 g / 10 min, dioxolane monomer weight content 5%, unstable terminal group content 1000 mg / kg;
[0271] Formaldehyde absorbent: 0.5 parts, melamine or melamine derivatives;
[0272] Macromolecular formaldehyde absorbent: 0.5 parts, copolyamide resin containing hydrazide end groups, powder, particle size 10 μm;
[0273] Composite antioxidant: 0.20 parts, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] / tris(2,4-di-tert-butylphenyl) phosphite, the weight ratio of the three components is 1:1:1;
[0274] Compound acid-absorbing antacid: 1.50 parts, calcium stearate / magnesium oxide / Mg6Al2(OH) 16 CO3·4H2O, the ratio of the three is 3:4:2, magnesium oxide and Mg6Al2(OH) 16 The particle size of CO3·4H2O is 2 μm;
[0275] Anti-penetration agent: 1.50 parts, polyethylene glycol, molecular weight 2000g / mol;
[0276] Lubricant: 0.05 parts, glyceryl monostearate;
[0277] Crystal nucleating agent: 0.5 parts, fumed silica / talc, the weight ratio of the two components is 1:1;
[0278] The above materials are added into a high-speed mixer for premixing, and then melted, mixed, extruded and granulated by a twin-screw extruder to obtain a polyoxymethylene composition; wherein the processing temperature is 200°C and the screw speed is 600r / min. The twin-screw extruder used is a large-capacity evaporation (multi-stage exhaust) devolatilization twin-screw unit with a length-to-diameter ratio of 50:1. During operation, the vacuum degree of each exhaust section of the twin-screw extruder is -0.07MPa.
[0279] Comparative Example 10
[0280] The polyoxymethylene composition ratio is as follows:
[0281] Copolymer polyoxymethylene resin: 100 parts, melt index 9.0 g / 10 min, dioxolane monomer weight content 5%, unstable terminal group content 1000 mg / kg;
[0282] Formaldehyde absorber: 0.05 parts, melamine or melamine derivatives;
[0283] Macromolecular formaldehyde absorbent: 0.05 parts, copolyamide resin containing hydrazide end groups, powder, particle size 10 μm;
[0284] Composite antioxidant: 0.20 parts, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] / tris(2,4-di-tert-butylphenyl) phosphite, the weight ratio of the three components is 1:1:1;
[0285] Compound acid-absorbing antacid: 2 parts, magnesium stearate / zinc oxide / Mg6Al2(OH) 16 Cl2·4H2O, the ratio of the three is 3:3:2, zinc oxide / Mg6Al2(OH) 16 The particle size of Cl2·4H2O is 1 μm;
[0286] Anti-penetration agent: 2 parts, polyethylene glycol, molecular weight 100000 g / mol;
[0287] Lubricant: 0.05 parts, glyceryl monostearate;
[0288] Crystal nucleating agent: 0.6 parts, fumed silica / talc, the weight ratio of the two components is 1:1;
[0289] The above materials are added into a high-speed mixer for premixing, and then melted, mixed, extruded and granulated by a twin-screw extruder to obtain a polyoxymethylene composition; wherein the processing temperature is 170-240°C, and the screw speed is 600r / min. The twin-screw extruder used is a large-capacity evaporation (multi-stage exhaust) devolatilization twin-screw unit, with a length-to-diameter ratio of 50:1, and the vacuum degree of each exhaust section of the twin-screw extruder during operation is -0.07MPa.
[0290] Comparative Example 11
[0291] The polyoxymethylene composition ratio is as follows:
[0292] Copolymer polyoxymethylene resin: 100 parts, melt index 9.0 g / 10 min, dioxolane monomer weight content 5%, unstable terminal group content 1000 mg / kg;
[0293] Formaldehyde absorbent: 0.02 parts, melamine or melamine derivatives;
[0294] Macromolecular formaldehyde absorbent: 0.05 parts, copolyamide resin containing hydrazide end groups, powder, particle size 10 μm;
[0295] Composite antioxidant: 0.30 parts, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] / tris(2,4-di-tert-butylphenyl) phosphite, the weight ratio of the three components is 1:1:1;
[0296] Lubricant: 0.05 parts, glyceryl monostearate;
[0297] Crystal nucleating agent: 0.6 parts, fumed silica / talc, the weight ratio of the two components is 1:1;
[0298] The above materials are added into a high-speed mixer for premixing, and then melted, mixed, extruded and granulated by a twin-screw extruder to obtain a polyoxymethylene composition; wherein the processing temperature is 170-240°C, and the screw speed is 600r / min. The twin-screw extruder used is a large-capacity evaporation (multi-stage exhaust) devolatilization twin-screw unit, with a length-to-diameter ratio of 50:1, and the vacuum degree of each exhaust section of the twin-screw extruder during operation is -0.07MPa.
[0299] The properties of the polyoxymethylene composition materials obtained in the examples and comparative examples were tested using the following method. The results are shown in Table 1.
[0300] The fuel resistance is determined as follows:
[0301] Use an electronic balance to weigh the mass of the polyoxymethylene standard sample and then put it into a 500mL sample bottle; measure 500mL of standard gasoline and add it to the sample bottle; place the sample bottle in a 50-70℃ water bath and maintain the constant temperature for 150-300h; wash the corroded standard sample with deionized water, weigh the sample after drying; calculate the mass change before and after the test.
[0302] The method for determining acid corrosion resistance is as follows:
[0303] First, concentrated hydrochloric acid with a concentration of 36% to 38% is diluted with deionized water to a solution pH value of ≤1.0.
[0304] Use an electronic balance to weigh the mass of the polyoxymethylene standard sample, and then put it into a 500mL sample bottle; measure 500mL of hydrochloric acid solution and add it to the sample bottle; place the sample bottle in a 45-55℃ water bath and maintain the constant temperature for 100-200h; wash the corroded standard sample with deionized water, weigh the sample after drying; calculate the mass change before and after the test.
[0305] The thermal stability was determined as follows:
[0306] The time required for the polyoxymethylene sample to lose 5% of its weight at 250° C. (in air atmosphere) is measured by a TG thermogravimetric analyzer. The time is expressed in minutes. The longer the time, the better the thermal stability.
[0307] The method for determining the color space L*a*b of the polyoxymethylene composition is as follows:
[0308] The b value in Lab represents the yellow-blue color. When the b value is positive, it means that the sample is yellowish; when the b value is negative, it means that the sample is blue; when the b value is 0, it means that the sample color is white. The b value of the polyoxymethylene sample particles was measured using a desktop high-precision spectrophotometer.
[0309] Table 1
[0310]
[0311]
[0312] It can be seen from the test data in Table 1 that the polyoxymethylene composition materials prepared by the synergistic effect of the composite acid-absorbing antacid and the anti-penetration agent in Examples 1 to 9 of the present application have a fuel resistance retention rate of more than 85%, with a maximum of 90.2%, and an acid resistance retention rate of more than 81.9%, with a maximum of 87.9%; the thermal stability time is 38.4 to 40.8 min; the b value is 3.1 to 4.39; the above test data show that the polyoxymethylene composition material prepared in the present application has excellent acid corrosion resistance and fuel resistance, good thermal stability and very low yellowness.
[0313] Comparative Examples 1 to 3 only use two compound antacids, but the fuel resistance is only 62.5% to 67%, and the acid resistance is 59.1% to 64.7%, which is more than 20% less than the embodiment of the present application, and the thermal stability is about 10 minutes less than the embodiment of the present application, and the yellowness value is more than 2 times that of the embodiment of the present application. It shows that for antacids, the use of the three antacids selected in this application can significantly improve the fuel resistance and acid resistance as well as the thermal stability and yellowness of the polyoxymethylene composite material.
[0314] Comparative Examples 4 to 6 use only one antacid, and their fuel resistance and acid resistance are much worse than those of the present application, indicating that the effect of using one antacid cannot achieve the synergistic effect of a combination of three antacids.
[0315] Comparative Example 7 does not use an antacid, and its fuel resistance and acid resistance are substantially only 50% of those of the present application.
[0316] Comparative Examples 8 to 10 use the three composite antacids prepared in the present application, but the anti-permeability is improved by adding polyethylene glycol or not. The fuel resistance and acid resistance of the obtained polyoxymethylene composite material are more than 10% lower than those of the present application, but the yellowness is very large; this shows that the addition of the anti-permeability agent can cooperate with the composite antacid of the present application to improve the fuel resistance, acid resistance, thermal stability and color quality.
[0317] Comparative Example 11 does not add antacids and anti-penetration agents, and its fuel resistance is 50% less than that of the present application, its acid resistance is 45% less than that of the present application, and its thermal stability is 15 minutes less than that of the present application. It is further explained that the present application can significantly improve the fuel resistance and acid resistance of the polyoxymethylene composite material by adding a composite antacid and an anti-penetration agent to the polyoxymethylene material, and both can be obtained by more than 85%.
[0318] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0319] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A polyoxymethylene composite material, characterized in that: The polyoxymethylene composition material comprises the following raw materials in parts by weight: Wherein, the composite acid-absorbing antacid is a compound of stearate, metal oxide and hydrated magnesium aluminum inorganic salt; The molecular formula of the hydrated magnesium aluminum inorganic salt is Mg 1-x Al x (OH)2A n- x / n ·mH2O.
2. The polyoxymethylene composite material according to claim 1, characterized in that: The weight ratio of the stearate, the metal oxide and the hydrated magnesium aluminum inorganic salt is (5-2): (5-2): (2-1); And / or, the particle size of the metal oxide and / or the hydrated magnesium aluminum inorganic salt is less than or equal to 5 μm.
3. The polyoxymethylene composite material according to claim 1 or 2, characterized in that: The stearate is selected from one or more of magnesium stearate, zinc stearate and calcium stearate; And / or, the metal oxide is selected from one or more of magnesium oxide, zinc oxide and calcium oxide; And / or, the Mg 1-x Al x (OH)2A n- x / n A in mH2O n- Select from NO 3- 、CO3 2- 、SO4 2- , Cl - One or more of .
4. The polyoxymethylene composite material according to any one of claims 1 to 3, characterized in that: The copolymer polyoxymethylene resin is copolymerized by trioxymethylene and dioxolane, and the weight percentage of the dioxolane is 1.5-5.0%; And / or, the melt index of the copolymer polyoxymethylene resin is 1.0 to 550.0 g / 10 min, and the unstable end group content thereof is less than or equal to 9000 mg / kg; And / or, the Mg 1-x Al x (OH)2A n- x / n ·mH2O is selected from Mg6Al2(OH) 16 CO3·4H2O、Mg6Al2(OH) 16 SO4·4H2O、Mg6Al2(OH) 16 (NO3)2·4H2O、Mg6A l2 (OH) 16 Cl2·4H2O.
5. The polyoxymethylene composite material according to any one of claims 1 to 4, characterized in that: The anti-penetration agent is vinyl polyethylene glycol ether; preferably, the molecular weight of the vinyl polyethylene glycol ether is 1000-100000 g / mol.
6. The polyoxymethylene composite material according to any one of claims 1 to 5, characterized in that: The composite antioxidant is composed of antioxidant A, antioxidant B and antioxidant C; the weight ratio of antioxidant A, antioxidant B and antioxidant C is (1-2):1:(0.5-2); Wherein, the antioxidant A is triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate; The antioxidant B is N,N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionyl)hexanediamine, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate or n-octadecylβ-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate; The antioxidant C is selected from tris(2,4-di-tert-butylphenyl) phosphite, dioctadecyl pentaerythritol diphosphite or bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite; Preferably, the composite antioxidant is selected from triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / N,N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine / tris(2,4-di-tert-butylphenyl) phosphite, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] pentaerythritol / tris(2,4-di-tert-butylphenyl) phosphite Triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / N,N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine / dioctadecyl pentaerythritol diphosphite, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / N,N-bis-(3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionyl) hexanediamine / bis(2,4-di-tert-butylphenol) Pentaerythritol diphosphite, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester / tris(2,4-di-tert-butylphenyl) phosphite, triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester / dioctadecyl pentaerythritol diphosphite, triethylene glycol bis-β -(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester / bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite and one or more of triethylene glycol bis-β-(3-tert-butyl-4-hydroxy-5-methylphenyl) propionate / β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate octadecyl alcohol ester / bis(2,4-di-tert-butylphenol) pentaerythritol diphosphite.
7. The polyoxymethylene composite material according to any one of claims 1 to 6, characterized in that: The formaldehyde absorbent is melamine and / or a derivative of melamine; And / or, the macromolecular formaldehyde absorbent is a copolyamide resin containing hydrazide end groups, which is in powder form, has a particle size of less than or equal to 55 μm, and a melting point of greater than or equal to 140° C.
8. The polyoxymethylene composite material according to any one of claims 1 to 7, characterized in that: The lubricant is N,N-ethylene bisstearamide and / or glyceryl monostearate; And / or, the crystal nucleating agent is talc and / or fumed silica; Preferably, the particle size of the talc is less than or equal to 5 μm, and the particle size of the fumed silica is less than or equal to 40 nm.
9. The method for preparing the polyoxymethylene composition material according to any one of claims 1 to 8, characterized in that: Step S1: obtaining various raw materials according to the formula, mixing them to form a mixed material; Step S2: Melting, mixing and granulating the mixed material to obtain the polyoxymethylene composition material.
10. The method for preparing the polyoxymethylene composition material according to claim 9, characterized in that: The melting temperature is 170-245°C; And / or, the operation process of step 2 is carried out in a twin-screw extruder, the screw speed is 20-600r / min, the aspect ratio of the twin screw is (25-70):1, and the vacuum degree of each exhaust section of the twin-screw extruder is ≤-0.07MPa.